ANALISIS CUSTOMER ENGAGEMENT TERHADAP KAFE DI KOTA TEGAL - Puput Dewi Anggraeni; Tantri Adithia Sabrina (STIE Pariwisata API Yogyakarta, 2021)
The development of the tourism sector in Indonesia is always accompanied by the development of the hotel industry, tourist attractions, restaurants and cafes, this is a complementary entity between tourist attractions, lodging places and places to eat. The rise of the cafe business in the city of Tegal has made many changes in various fields both social and economic, however it needs to be further investigated about customer engagement in various dimensions and indicators that greatly affect the sustainability and business development of a cafe from the perspective of tourism and hospitality. The purpose of this study was to determine the dimensions of customer engagement of cafes in Tegal City and measure the level of customer engagement based on the dimensions that have been formulated. This research is a quantitative research with descriptive analysis method. The population in this study is the cafe customers, amounting to 30 peoples. The instrument in this study used questionnaires. The results of this study indicate that customer engagement has three dimensions: customer satisfaction, brand trust and brand loyalty. The suggestions is to improve services, maintain product quality and good service. This step is expected to increase customer satisfaction so as to maintain brand trust and brand loyalty of the cafe itself in the future.